2011
DOI: 10.1051/0004-6361/201015931
|View full text |Cite
|
Sign up to set email alerts
|

Dipping in CygnusX-2 in a multi-wavelength campaign due to absorption of extended ADC emission

Abstract: We report results of one-day simultaneous multiwavelength observations of Cygnus X-2 using XMM, Chandra, the European VLBI Network and the XMM Optical Monitor. During the observations, the source did not exhibit Z-track movement, but remained in the vicinity of the soft apex. It was in a radio quiescent/quiet state of <150 μJy. Strong dip events were seen as 25% reductions in X-ray intensity. The use of broadband CCD spectra in combination with narrow-band grating spectra has now demonstrated for the first tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…showing a clear correlation with Z-track position (Hjellming et al 1990a). Similarly, Ba lucińska- Church et al (2011) found a 5σ upper limit of < 150 µJy at 5 GHz in e-EVN observations in 2009, May. Sco X-1 on the other hand has both radio-loud and radio-weak states and weak radio emission has been detected when on the FB (Hjellming et al 1990b).…”
Section: A Model For the Sco X-1 Like Sourcesmentioning
confidence: 76%
See 2 more Smart Citations
“…showing a clear correlation with Z-track position (Hjellming et al 1990a). Similarly, Ba lucińska- Church et al (2011) found a 5σ upper limit of < 150 µJy at 5 GHz in e-EVN observations in 2009, May. Sco X-1 on the other hand has both radio-loud and radio-weak states and weak radio emission has been detected when on the FB (Hjellming et al 1990b).…”
Section: A Model For the Sco X-1 Like Sourcesmentioning
confidence: 76%
“…In multi-wavelength observations of Cygnus X-2 in 2009 (Ba lucińska- Church et al 2011) a series of absorption edges below 1.4 keV remarkably had no detectable increase in depth during dips, showing that part of the continuum emission had to be extended so that part was not covered, while covered emission below 1.4 keV was completely removed.…”
Section: The Extended Adcmentioning
confidence: 99%
See 1 more Smart Citation
“…The sudden drops to a low flux mode appear to be of an entirely different nature than the dips in the X-ray dipper variety of LMXBs (e.g., White & Swank 1982;Smale et al 1988;Balucinska-Church et al 2011) as they do not show spectral changes in either soft X-rays (as shown in Section 6) or hard X-rays (see Tendulkar et al 2014). In general, based on the results of the X-ray spectral fits presented in Section 6, any interpretation that evokes obscuration/absorption is unlikely.…”
Section: −1mentioning
confidence: 94%
“…It has been proposed that these variations are due to progressive and partial covering of an extended ADC by an extended absorber (see Bałucińska-Church et al 2011;Church et al 2005Church et al , 1998, for example). Authors such as Boirin et al (2005) and Díaz Trigo et al (2006), on the other hand, propose that an ionized absorber can explain dipping and non-dipping intervals, without the need of an extended ADC.…”
Section: Variability and Dippingmentioning
confidence: 99%